Evaluating Weaknesses of “Perceptual-Cognitive Training” and “Brain Training” Methods in Sport: An Ecological Dynamics Critique - Renshaw, Ian; Davids, Keith; Araújo, Duarte; Lucas, Ana; Roberts, William M.; Newcombe, Daniel J.; Franks, Benjamin (Frontiers in Psychology, 2019)
The recent upsurge in “brain-training and perceptual-cognitive-training", proposing to improve isolated processes such as brain function, visual perception and decision-making, has created significant interest in elite sports practitioners, seeking to create an ‘edge’ for athletes. The claims of these related 'performance-enhancing industries' can be considered together as part of a process training approach proposing enhanced cognitive and perceptual skills and brain capacity, to support performance in everyday life activities, including sport. For example, the 'process-training industry' promotes the idea that playing games not only makes you a better player, but also smarter, more alert, and a faster learner. In this position paper we critically evaluate the effectiveness of both types of process-training programmes in generalizing transfer to sport performance. These issues are addressed in three stages. First, we evaluate empirical evidence in support of perceptual-cognitive process training, and its application to enhancing sport performance. Second, we critically review putative modularised mechanisms underpinning this kind of training, addressing limitations and subsequent problems. Specifically, we consider merits of this highly specific form of training, which focuses on training of isolated processes such as cognitive processes (attention, memory, thinking) and visual perception processes, separately from performance behaviors and actions. We conclude that these approaches may, at best, may provide some 'general transfer' of underlying processes to specific sport environments, but lack 'specificity of transfer' to contextualize actual performance behaviors. A major weakness of process training methods is their focus on enhancing performance in body “modules” (e.g., eye, brain, memory, anticipatory sub-systems). What is lacking is evidence on how these isolated components are modified and subsequently interact with other process “modules”, which are considered to underlie sport performance. Finally, we propose how an ecological dynamics approach, aligned with an embodied framework of cognition undermines the rationale that modularised processes can enhance performance in competitive sport. An ecological dynamics perspective proposes that the body is a complex adaptive system, interacting with performance environments in a functionally integrated manner, emphasising that the inter-relation between motor processes, cognitive and perceptual functions and the constraints of a sport task is best understood at the performer-environment scale of analysis.